1991
DOI: 10.1017/s0031182000062636
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the relationships in the pinewood nematode species complex (PWNSC) (Bursaphelenchus spp.) using a heterologous unc-22 DNA probe from Caenorhabditis elegans

Abstract: SUMMARYPine wilt is the most serious disease of native pines in Japan and potentially the most important nematode disease of conifers in the world. The pinewood nematode Bursaphelenchus xylophilus was found to be the causal agent. Difficulties arose with respect to the precise identity of some isolates of B. xylophilus and of similar species B. mucronatus and B. fraudulentus. Restriction enzyme analyses of repetitive DNA revealed bands specific for the species B. xylophilus, B. mucronatus and B. fraudulentus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…This pattern supports the suggestion that the two species are distinct, even though they are very similar to each other in morphology and biology, and have been regarded as 'a super species ' (de Guiran and Bruguier, 1989) or a pinewood nematode species complex (Webster et al, 1990;Abad et al, 1991). Kanzaki and Futai (2002) studied the phylogenetic relationships of the B. xylophilus group by DNA sequence analysis.…”
Section: Discussionsupporting
confidence: 68%
“…This pattern supports the suggestion that the two species are distinct, even though they are very similar to each other in morphology and biology, and have been regarded as 'a super species ' (de Guiran and Bruguier, 1989) or a pinewood nematode species complex (Webster et al, 1990;Abad et al, 1991). Kanzaki and Futai (2002) studied the phylogenetic relationships of the B. xylophilus group by DNA sequence analysis.…”
Section: Discussionsupporting
confidence: 68%
“…It was reported that B. mucronatus originated in Eurasia (Iwahaori et al 2002), so it can be regarded as a native species in China. These two species have very similar morphological and biological features, and have even been referred to as ''a super species'' (De Guiran and Bruguier 1989), or pinewood nematode species complex (Webster et al 1990;Abad et al 1991). These two nematodes feed on epithelial cells and reproduce in the resin canals of pine trees, or feed on symbiotic fungi of their hosts (such as blue-stain fungi, Ceratocystis spp.).…”
Section: Introductionmentioning
confidence: 99%
“…Tests available for the identification of B. xylophilus include the use of DNA hybridization probes (Abad et al ., ; Tares et al ., ) and various PCR procedures (Harmey & Harmey, ; Braasch et al ., , ; Hoyer et al ., ; Iwahori et al ., ; Mota et al ., ; Zheng et al ., ; Kang et al ., ; Matsunaga & Togashi, ; Burgermeister et al ., ; Cao et al ., ; Castagnone et al ., ; Jiang et al ., ; Leal et al ., ; Takeuchi et al ., ). When molecular tests are used for quarantine purposes to detect B. xylophilus in wood products, it is essential to recognise that both live and dead nematodes can be detected by these tests.…”
Section: Identificationmentioning
confidence: 98%